Efektivitas Teknik Pelvic Rocking Dengan Birthing Ball Terhadap Lama Persalinan Kala I Pada Ibu Bersalin Di Wilayah Kerja Puskesmas Bahu Kota Manado - Sitti Aisya Nazwa S. Bolong; Irne Wida Desiyanti; Hindun Rahim (Universitas Pahlawan Tuanku Tambusai, 2025)
Prolonged first stage of labor increases the risk of complications for both mother and baby. Pelvic rocking with birthing ball is a non-pharmacological method that is believed to accelerate cervical dilation and shorten labor duration. This was conducted to determine the effectiveness of these techniques on laboring mothers at the Bahu Health Center. This research method uses a Quasi-Experimental design with a post-test only design approach. The sample consisted of 34 primigravida mothers in the first stage of labor, divided into two groups: intervention (pelvic rocking + birthing ball) and control (walking). Sampling is done with total sampling technique.. Data were collected using observation sheets and partographs. Data analysis using Welch’s t-test due to non-homogeneous variance. The result showed that the mean duration of first stage labor in the intervention group was 232.41 minutes, while the control group was 323.88 minutes. Time difference of 91.47 minutes with a significance value of p = 0,002 (p < 0,05) indicating a significant difference. Pelvic rocking with a birthing ball is effective in accelerating labor time of the first stage. It is recommended that healthcare workers implement these techniques as a non-pharmacological alternative in maternity care.